2021
DOI: 10.1007/s00125-021-05501-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered cellular localisation and expression, together with unconventional protein trafficking, of prion protein, PrPC, in type 1 diabetes

Abstract: Aims/hypothesis Normal cellular prion protein (PrP C ) is a conserved mammalian glycoprotein found on the outer plasma membrane leaflet through a glycophosphatidylinositol anchor. Although PrP C is expressed by a wide range of tissues throughout the body, the complete repertoire of its functions has not been fully determined. The misfolded pathogenic isoform PrP Sc (the scrapie form of PrP) is a causative agent of neurodegenerative prion diseases. The aim of this study is to evaluate PrP C localisation, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 59 publications
(85 reference statements)
0
6
0
1
Order By: Relevance
“…In this context, it is of interest to highlight that recently, the Wasserfall group (48) showed an increased frequency of cellular prion proteins in pancreas specimens from people with T1D and that, earlier, Strom and collaborators (49) demonstrated in two rodent models that altered metabolism of cellular prion protein in β cells associated with glucose dysregulation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this context, it is of interest to highlight that recently, the Wasserfall group (48) showed an increased frequency of cellular prion proteins in pancreas specimens from people with T1D and that, earlier, Strom and collaborators (49) demonstrated in two rodent models that altered metabolism of cellular prion protein in β cells associated with glucose dysregulation.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the neutrophil, platelet, and immune cell activation related pathways, the differentially expressed proteins and phosphoproteins were enriched for other biological processes and KEGG pathways related to prion disease and multiple neurodegenerative diseases. In this context, it is of interest to highlight that recently, the Wasserfall group (48) showed an increased frequency of cellular prion proteins in pancreas specimens from people with T1D and that, earlier, Strom and collaborators (49) demonstrated in two rodent models that altered metabolism of cellular prion protein in β cells associated with glucose dysregulation.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in insulin-positive alpha and beta cells of patients with and without type 1 diabetes, PrP C was found in the plasma membrane and the ER but not in Golgi, possibly indicating UPS by the Golgi bypass. In this work, the authors suggest that the PrP C ’s Golgi bypass observed in the human pancreas could be through HSP70/DNAJC14 or GRASP55 ( Hiller et al, 2021 ). As aforementioned, PrP C associates with the HSP70/90 co-chaperone STI1/HOP in the cell surface ( Lopes et al, 2005 ; Rosenzweig et al, 2019 ), which could indicate a greater tendency of secretion to be via HSP70/DNAJC14, although this hypothesis must be tested and the mechanism for PrP C UPS needs to be clarified.…”
Section: Unconventional Protein Secretion In Brain Tumorsmentioning
confidence: 86%
“…There was a statistical significance between PrP C expression and DM. Although several studies demonstrated associations with PrP C and DM [ 37 , 38 , 39 ], there have been no reports that the expression of PrP C in HCC tissues is related to DM. Oskarsson et al demonstrated that intravenous injection of synthetic islet amyloid polypeptide (IAPP) aggregates can accelerate IAPP aggregate formation in islets in a rodent model of type 2 DM [ 40 ].…”
Section: Discussionmentioning
confidence: 99%